Colostrum and serum protein levels in water buffaloes - da Silva, Moacir Cerqueira; de Queiroz, Waldenei Travassos; Lau, Hugo Didonet; Vale, William Gomes (Pesquisa Agropecuaria Brasileira, 1993)
Blood serum samples and colostrum of 17 Murrah water buffalo cows (Bubalus bubalis) were examined at birth as well as their offspring before the ingestion of colostrum at 1, 3, 6, 12, 24, 48, 72 and 96 hours after birth to determine the failure in the passive transfer of antibodies. The parameters studied included the total protein (TP), albumin (ALB), alphaglobulin (a GLO), beta-globulin (b GLO) and gamma-globulin (g GLO) concentration in the serum and colostrum through refractometry and biuret method and protein fractions, separated by electro-phoresis. At birth the calves presented a hypogammaglobulinemia or agammaglobulinemia followed by a considerable increase in the serum levels of TP and g GLO from birth until 96 hours after birth (r=0.9278). However by electrophoresis it could be detected six hours after colostrum ingestion and antibody levels thus being comparable to those in the adult animals, 3.06 g/100 ml. Calves which had suckled showing values up to 0.71 g/ml suggest a failure in the passive transfer, g GLO values between 0.85 and 1.71 g/100 ml suggest a partial failure and levels above 3.06 g/100 ml indicate an appropriate transfer of antibodies present in the colostrum, a situation of extreme importance for the survival of the newborn calf due to the high content (approximately 82%) of g GLO.